2011
DOI: 10.5306/wjco.v2.i8.311
|View full text |Cite
|
Sign up to set email alerts
|

Dickkopfs and Wnt/β-catenin signalling in liver cancer

Abstract: Liver cancer is the fifth and seventh most common cause of cancer in men and women, respectively. Wnt/β-catenin signalling has emerged as a critical player in both the development of normal liver as well as an oncogenic driver in hepatocellular carcinoma (HCC). Based on the current understanding, this article summarizes the possible mechanisms for the aberrant activation of this pathway with specific focus on HCC. Furthermore, we will discuss the role of dickkopfs (DKKs) in regulating Wnt/β-catenin signalling,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
41
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 161 publications
(193 reference statements)
3
41
0
Order By: Relevance
“…The Wnt pathway drives proliferation, maintains survival and promotes stemness in cancer cells (Klaus and Birchmeier 2008), and plays a well-known role in HCC tumorigenesis ( Whittaker et al 2010;Fatima et al 2011). Overall, 62.5% of tumors in the cohort contain genomic alterations composed of SNV and CNV affecting core components of the Wnt pathway (Fig.…”
Section: Frequently Altered Cancer Pathwaysmentioning
confidence: 99%
“…The Wnt pathway drives proliferation, maintains survival and promotes stemness in cancer cells (Klaus and Birchmeier 2008), and plays a well-known role in HCC tumorigenesis ( Whittaker et al 2010;Fatima et al 2011). Overall, 62.5% of tumors in the cohort contain genomic alterations composed of SNV and CNV affecting core components of the Wnt pathway (Fig.…”
Section: Frequently Altered Cancer Pathwaysmentioning
confidence: 99%
“…Wnt/β-catenin signaling has emerged as a critical player in both the development of normal liver as well as an oncogenic driver in hepatocellular carcinoma (HCC) [19, 20]. It has been reported that 40%-70% of HCC patients have tumors with high levels of β-catenin accumulation [21-24].…”
Section: Fzd7 In Cancermentioning
confidence: 99%
“…Mutations in the β-catenin gene were found in 12-26% of HCCs, while mutations in APC and Axin2 are very rare [25]. Recent studies indicate that dysregulation of Wnt/β-catenin signaling in HCC is also due to the aberrant epigenetic regulation of several Wnt signaling antagonists [26-30] and/or the up-regulation of cell surface Wnt proteins and their receptors [20]. The Fzd7 steady-state mRNA levels are up-regulated in hepatitis B, C, and nonviral-induced HCC cell lines and mouse models [27, 31, 32].…”
Section: Fzd7 In Cancermentioning
confidence: 99%
“…One such relevant pathway is the Wnt/ β -catenin signaling cascade which plays a decisive role in cell fate, favoring cell proliferation over apoptosis. Accumulating evidence has shown that the canonical Wnt/ β -catenin pathway is frequently activated in HCC and responsible for initiation and progression of the disease [1316], and this pathway could be an attractive and viable target for chemoprevention and therapy of HCC [17–19]. …”
Section: Introductionmentioning
confidence: 99%